Education as a Tool for Control vs. Development Among Indigenous Peoples: The Case of Bedouin Arabs in Israel - Abu-Saad, Ismael (Hagar: Studies in Society and Culture, 2001)
In the lost few decades, indigenous education movements characterized by indigenous control over the content, qualm and delivery of educational services have developed around the world. They are also characterized by interculturality based on equipping their students with the knowledge and skills they need to function and develop in their own culture as well as in other cultural settings in the same sociopolitical framework. In this paper. I will discuss the case of the Negev Bedouin, who constitute a part of the indigenous Palestinian Arab people and who came under the control of the state of Israel in 1948. As with other indigenous minorities, education maintains the potential either to be an impediment or a key to their development. In this paper, I will briefly describe the changes the Bedouin have undergone since the establishment of the state of Israel and then discuss the structure of the educational system and ways in which it has affected the development of the Negev Bedouin. Finally I will discuss what must be done to transform the educational system into a tool for serving and strengthening the community and I will then suggest a number of educational strategies for development.